DESIGN OF EARLY FLOOD DETECTION (EFDe) SYSTEM BASED ON IoT FOR FLOOD VOCATIONAL AREAS - Wan Alamsyah; Eka Mutia; Yulina Ismida; Asmadi Suria; Rachmad Almi Putra (Jurnal Neutrino: Jurnal Fisika dan Aplikasinya)
There is an early flood detection tool that has been successfully designed called the Early Flood Detection (EFDe) a system that uses the Internet of Things system which can be accessed by the users through a browser or an Android smartphone. In general, this tool has an accurate sensor response to the water level reading by the sensor. The time needed for the sensor to send data to the server is 10-15 seconds. The speed of this delivery time is influenced by several factors, including sensor response, server response, and the cellular network used. The EFDe system is equipped with an alarm around the location and has 10-15 second response when the indicator shows FLOOD POTENTIAL and will not stop until the signal changed to SAFE. This EFDe System is equipped with a solar panel and solar control charger and has an independent energy source that comes from the sun and stored in batteries. That is why the EFDe system is able to send information in real-time.